1975
DOI: 10.1017/s0001566000010515
|View full text |Cite
|
Sign up to set email alerts
|

The Gm and Inv Factors in Rheumatoid Arthritis

Abstract: The Gm(1), Gm(2), Gm(4), Gm(12), and Inv(1) factors were studied in the sera of 56 patients suffering from rheumatoid arthritis and 26 from various rheumatic diseases, by the hemagglutination inhibition test, using optimally reacting mixtures of Ragg and Nagg sera. The distribution of these factors was found to agree with that of healthy Greeks. No correlation was found between hypergammaglobulinemia and the discovery of the Gm(1) and Inv(1) factors. The presence of the rheumatoid factor was independent of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Polyclonal RFs from persons with RA share the cross-reactive idiotypes of monoclonal RFs (15). Reports of previous studies using the kappa allotypic marker Km (1) showed no significant association with RA in a study of British subjects (16), but in a Greek population, there was a trend toward association (17). I have found that there is an increased frequency of the homozygous C, genotype in RA (18), particularly in HLA-DR4 negative individuals (19).…”
mentioning
confidence: 65%
“…Polyclonal RFs from persons with RA share the cross-reactive idiotypes of monoclonal RFs (15). Reports of previous studies using the kappa allotypic marker Km (1) showed no significant association with RA in a study of British subjects (16), but in a Greek population, there was a trend toward association (17). I have found that there is an increased frequency of the homozygous C, genotype in RA (18), particularly in HLA-DR4 negative individuals (19).…”
mentioning
confidence: 65%